Crítica da concepção de criança, de educação e de cultura corporal na educação infantil: análise dos documentos oficiais - Dias, Roseane Suzart Leite (2015)
The aim of this study is to investigate the concept of body culture in children's education and it is justified by the importance that the body culture has for childhood development. Thus, our objective is to verify the concept of body culture present in Children's Education through the National Curriculum Referential analysis for Children's Education and the National Curriculum Guidelines for Children's Education; Identify the concept of human being/child, regular education/children's education that the National Curriculum Reference for Children's Education, the National Curriculum Guidelines for Children's Education and the National Policy for Children's Education support. Our hypothesis is that there is no scientific concepts in documents dealing on body culture and that this lack of scientific undertakes the process of learning in kindergarden. Therefore, our investigation aim to answer the following issues: What is the concept of human being/child and education/children's education wich sustain those official documents for teaching in Children's Education? In particular, what is the concept of body culture they assume? The starting point to build this work was given by the defense of the historical dialectical materialist knowledge's theory. Whereas research technique, we used the content analysis. We have presented the concept of human being, analyzed how this concept directs the course of training; then we have treated the specifics of child development, pedagogical concepts present in Children's Education institutions and the role of teachers in this development process; we have analyzed the concept of body culture and its role in the development process in childhood; after that, we have presented the analysis of the documents. Finally, we have found that the guiding documents of early Children's Education originate from a biologicist concept of development and are based on the pedagogy of "learning to learn". In conclusion, we seek to summarize the analysis results, we criticize the pedagogy of "learning to learn" and point out the importance of the children own the elements of body culture from an early age, realizing that they must be transmitted based on scientific concepts .